Community Perception of Wild Boar Meat Consumption Based on a Halal Perspective - Jannah, Roudhotul Lu'luul; Siswara, Hamzah Nata; Erwanto, Yuny; Cahyowati, Meireni; Anwar, Chairil (Fakultas Peternakan, Universitas Padjadjaran, 2026)
Consuming wild boar meat is still popular among the people of Sekaran Village, Tuban Regency, even though the religion they believe in is Islam. The aim of this research is to investigate people's perceptions of the consumption of wild boar meat, to know the background of people who consume wild boar meat and to know the distribution of wild boar meat in the Tuban area. This research was carried out in several stages, namely observation, interviews using a sample of 100 respondents and documentation. Perception measurement uses a likert scale with an assessment score of 1-3 scores and data processing uses descriptive statistical analysis and correlation analysis. The results showed that the relationship between wild boar meat consumption has a positive effect on the halal knowledge perspective, with a significant value of 0.043 (p<0.05). This means that people know that consuming wild boar meat is not Halal, but people still consume it. There is a belief and perception among local people that consuming wild boar meat is a good and proud thing. They are also known that consuming wild boar meat is not good for health and distributing wild boar meat was contrary with government regulations but they still consume and distribute it. Geographical position this village where far from city center also become a reason consuming wild boar meat. Wild boar meat consumption is influenced by price, income, taste and distribution of wild boar meat. The distribution of wild boar meat is not only in the Tuban Regency area, but the demand for wild boar meat is greater in Blora, Central Java.